PENGARUH HARGA KOMODITAS BAHAN POKOK TERHADAP INFLASI BARANG BERGEJOLAK (VOLATILE FOOD) DI KOTA PEKANBARU PERIODE 2019 - Rafli, Hasan Andifa; Antony, Mayes; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine all the major effects of staple commodities on volatile food inflation in Pekanbaru City for the period of 2019. This study uses independent variables which consists of prices of rice, red chilies, shallots, sugar, cooking oil, chicken, beef, eggs, garlic and the dependent variable is volatile food inflation. The data used in this study are monthly data for the period 2019. The analysis method used descriptive quantitative and partial or simultaneous analysis with multiple linear regression with the OLS (Ordinary Least Square) approach which is processed by using E-Views version 10. The test results show that the prices of basic commodities simultaneously have a significant effect on volatile food inflation. Meanwhile, shallots have a positive effect and sugar has a negative and significant effect on volatile food inflation, rice has a positive effect, red chilies have a positive effect, cooking oil has a positive effect, chicken has a positive effect, beef has a positive effect, eggs have a negative effect, Garlic has a positive and insignificant effect on volatile food inflation. In addition, the value obtained from the adjusted R2 is 97.90%.Keywords: volatile food inflation, staple food commodity prices